First‐Generation Subporphyrinatoboron(III) Sensitizers Surpass the 10 % Power Conversion Efficiency Threshold. Issue 35 (2nd August 2016) - Copley, Graeme; Hwang, Daesub; Kim, Dongho; Osuka, Atsuhiro
Abstract: Subporphyrinatoboron(III) (SubB) sensitizers were synthesized for use in dye‐sensitized solar cells (DSSCs). The prototype, which comprises a sterically demanding 3, 5‐di‐ tert ‐butylphenyl scaffold, a meso‐ethynylphenyl spacer, and a cyanoacrylic acid anchoring group, achieved an open‐circuit voltage V OC of 836 mV, short‐circuit current density J SC of 15.3 mA cm −2, fill factor of 0.786, and a photon‐to‐current conversion efficiency of 10.1 %. Such astonishing figures suggest that a bright future lies ahead for SubB in the realm of DSSCs. Abstract : Sensitivity training : The first generation of subporphyrinatoboron(III)‐based molecular sensitizers were tested in dye‐sensitized solar cells (DSSCs). The most advanced prototype achieved a photon‐to‐current conversion efficiency value of 10.1 %. Such an astonishing figure suggests the potential for subporphyrinatoboron compounds in the field of DSSCs.